John Locke on Reading the Bible: Rational Obscurity and the Lockean “Rule” - Brown, Julia (2023)
This essay resists the tendency to separate Lockean reason from revelation, and his political concerns from his Christian theology. Rather than a repudiation, in significant ways, Locke’s Paraphrase and Notes on the Epistles of St. Paul is the application of his methodological or hermeneutic approach to reading scripture laid out in the Essay Concerning Human Understanding. While the fundamental articles of Christianity were “plain” and “clear” in the gospels, requiring minimal interpretation, far more labor was required to render Paul’s sense “plain” and “clear.” Rather than a simplistic notion of doctrinal minimalism, Locke’s Christianity amplified order, duty, and obedience. It is his commitment to the interdependence of faith and reason which grounds Locke’s conviction that expressions of faith contrary to reason and destructive of civil order exceeded the bounds of legitimate religious expression.
Keywords: Obedience; Sincerity; Religious Toleration; scriptural politics; Seventeenth Century; scriptural hermeneutics; John Locke